2022
DOI: 10.11591/ijece.v12i3.pp2955-2962
|View full text |Cite
|
Sign up to set email alerts
|

Increasing electrical grid stability classification performance using ensemble bagging of C4.5 and classification and regression trees

Abstract: <span>The increasing demand for electricity every year makes the electricity infrastructure approach the maximum threshold value, thus affecting the stability of the electricity network. The decentralized smart grid control (DSGC) system has succeeded in maintaining the stability of the electricity network with various assumptions. The data mining approach on the DSGC system shows that the decision tree algorithm provides new knowledge, however, its performance is not yet optimal. This paper poses an ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
0
0
Order By: Relevance
“…Where is the Research Result Method C4.5 To measure the age classification based on the results of the dominant age decision tree algorithm and the accuracy of the 2017-2021 data. As in previous research shows that the decision tree algorithm provides new knowledge [6] and the experimental results C4.5 also confirms that the most influential instant data attribute [7].…”
Section: Introductionsupporting
confidence: 76%
“…Where is the Research Result Method C4.5 To measure the age classification based on the results of the dominant age decision tree algorithm and the accuracy of the 2017-2021 data. As in previous research shows that the decision tree algorithm provides new knowledge [6] and the experimental results C4.5 also confirms that the most influential instant data attribute [7].…”
Section: Introductionsupporting
confidence: 76%
“…Metode Classification and Regression Tree (CART) merupakan sebuah algoritma yang digunakan untuk memproduksi model klasifikasi atau regresi dengan mengategorikan data ke dalam kelas atau nilai yang sesuai dengan pertanyaan-pertanyaan yang diajukan secara bertahap. CART memecah data menjadi beberapa bagian yang semakin kecil dengan cara mengambil kondisi yang paling bermanfaat untuk memisahkan data ke dalam kelas atau nilai yang sesuai [12], [13]. Kriteria standar yang digunakan CART pada scikit adalah kriteria Gini Index.…”
Section: B Decision Treeunclassified
“…The authors observed that the battery is acting as a source while the PLN and solar cells are providing the energy, or vice versa, and just one bus at the load is in an unstable or dangerous state. Aziz and Lawi [24] proposed ensemble ML methods for electrical grid stability and achieved good accuracy. The authors experimented with C 4.5 and CART algorithms and reported good results.…”
Section: Introductionmentioning
confidence: 99%